THE USE OF CONTEXTUAL SEMANTIC ANALYSIS IN READING EXTENSIVELY A NOVEL AT 6th SEMESTER OF ENGLISH EDUCATION DEPARTMENT OF FKIP UNISMUH MAKASSAR - Hamid, Radiah (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2017)
This research is aimed to find out how the use of Contextual Semantic Analysis could  be implemented in learning the Extensive Reading at the English Students of the Sixth Semester of English Education Department of Unismuh Makassar. Therefore, the research described the students’ perception and understanding on Contextual Semantic Analysis and its positive influence on their application of comprehending the meaning of difficult words or sentences in reading extensively a novel. The method used in this research is Descriptive Method.  This research attends to describe the relation among the students’ perception on Contextual Semantic Analysis, symbolized with X and their application in comprehending the meaning of difficult words symbolized with Y. The data collecting has been done through questionnaire and reading comprehension test. Descriptive analysis was employed to analyse the data collected. The result of this research shown that most of students (60%) have good perception and understanding on Contextual Semantic Analysis and influence their application of Contextual Semantic Analysis in comprehending the meaning of difficult words in reading extensively a novel at 6th Semester of English Education Department Muhammadiyah University of Makassar, it was shown in correctness level the students achieved on 80% until 95% with the meaning of the dictionary. This result is also expected to be useful practically  in the  Extensive Reading, because it is not suggested to open dictionary and by knowing and using this analysis, the students are expected to make the language learning of Extensive Reading  be pleasure and enjoyable.